2005
DOI: 10.1016/j.jana.2005.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Support Services Provided by a Community-Based AIDS Service Organization on Persons Living With HIV/AIDS

Abstract: This study examined demographic, health-related, social support, and service utilization characteristics of clients with high and low use of a community-based AIDS service organization in Canada. The study confirmed that the organizations' services were reaching the most vulnerable persons living with HIV/AIDS. It found that a significantly greater number of high users compared with low users were single, lived alone, and reported poorer health. The similarity in functional health status and depression between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Gielen et al (2001) and similarly found access to social support to be important in enhancing the QOL of PLWA, while Crook et al (2005) and Makoae et al (2005) highlight the importance of communitybased support services. Yet, access to such support mechanisms may on the one hand be dependent on disclosure (D'Angelo et al, 2001;Klitzman et al, 2004).…”
Section: The Heart In Haartmentioning
confidence: 97%
“…Gielen et al (2001) and similarly found access to social support to be important in enhancing the QOL of PLWA, while Crook et al (2005) and Makoae et al (2005) highlight the importance of communitybased support services. Yet, access to such support mechanisms may on the one hand be dependent on disclosure (D'Angelo et al, 2001;Klitzman et al, 2004).…”
Section: The Heart In Haartmentioning
confidence: 97%
“…First, nongovernmental organizations can provide needed services to individuals, either distinct from the state or as a conduit for governmentfunded programs (Crook et al, 2005;Wilson et al, 2012). Second, actors in the third sector also can affect a community's health for the better by ensuring government accountability, advocating for government programs that address the health needs of disadvantaged populations, and by working for inclusion of those groups' voice in public policy, particularly in developing countries (Turiano and Smith, 2008;Spicer et al, 2011).…”
Section: Why Should Civil Society Matter For Health?mentioning
confidence: 99%
“…A Canadian study reported a reduced sense of isolation, increased knowledge of their illness and how to live with it, and improved quality of life as a result of using services from community-based AIDS organizations [7]. Studies show that receipt of support or ancillary services such as case management, mental health treatment, substance abuse treatment, housing assistance and transportation are significantly associated with early entry into and retention in HIV care [30].…”
Section: Discussionmentioning
confidence: 99%
“…Mor and colleagues reported that those who are white, male, and non-intravenous drug users have higher rates of outpatient clinic/physician use, whereas those who are nonwhite, female, and intravenous drug users have higher rates of emergency room use [6]. Crook and colleagues found that those people who are single, lived along, and reported poorer health have a higher utilization of a community-based AIDS service organization [7]. Uphold and Mkanta conducted a literature review and found a list of factors related to use of health care services among PLWH, including predisposing factors (eg: race, gender and injection drug use), enabling factors (eg: insurance, social support systems and housing), clinical factors (eg: immune status symptoms and depression), and contextual factors (eg: characteristics of clinicians and urban/rural residence) [8].…”
mentioning
confidence: 99%